The Research on Political Elites: Steady vs. Modern Theories - Matushenko, Oleksandra (The Copernicus Journal of Political Studies, 2018)
The purpose of the article is to address an existing challenge of conducting the research on political elites in modern societies, particularly in the emerging democracies. In addition to a significant gap between theoretical and empirical data, there is also no common vision of the best approach to the research on political elites, especially in transition countries. Most of all, it is caused by the absence of unified common view on the role and distinct functions of political elites in emerging democracies by the scientific world. Consequently, there is a problem with appropriate estimation and conducting analyses of elites’ actions, their weight, and strategy in decision making process towards or backwards to establishing democratic institutions and implication of democratic values. Thus, the article is to describe and analyse main divergence of views on the role, scope and dimension of research of political elites, provided by different theories, namely Marxist one, the classic political elites’ theory and the theory of democratic elitism in accordance with the challenges and requirements of the realities of the current political process. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14760